EFEKTIVITAS TERAPI MUSIK KLASIK TERHADAP PERUBAHAN PERILAKU AGRESIF PADA ANAK DENGAN AUTISME DI SLB-B DAN AUTIS TPA BINTORO PATRANG JEMBER - Zidny Yuris Yuhbaba (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2013)
Music therapy is the use of music as therapeutic tools to fix, maintain, develop physical, mental, emotional health in particular. This research is Quasi Experiment, without using a control group using the design of the study one group pretest posttest. Conducted a pretest (observation) to determine the level of aggression prior to treatment, then do posttest (observation) to determine the level of aggressiveness after treatment so that it can be seen the extent to which the effectiveness of classical music therapy against aggressive behavior in children with autism in SLB-B and Autism TPA Bintoro, Patrang, Jember. Overall study population was composed of 20 students of SLB-B and Autism TPA Bintoro, Patrang, Jember. Sampling by means of purposive sampling. The sampling is based on a certain considerations made by the researchers themselves, based on the characteristics or traits (goals / issues) population that has been previously known by the researchers. Sebanyk found 10 children with autism as the sample in this study. The data was collected by direct observation on the respondent is a child with autism in special schools Patrang Bintoro Jember. Observations made using the observation chart observation of aggressive behavior by using a check-list according to Delut who was adopted from the WHO. Based on the analysis of the data processed using the Wilcoxon shows there are significant effect between the level of aggressiveness of children with autism before and after therapy is given to classical music. This is indicated by the value of p = 0.005 (p <0.05). Thus, classical music therapy is effective against changes in aggressive behavior in children with autism. This study can be used as the basic foundation for SLB-B and Autism Bintoro Patrang TPA can socialize and continue the music therapy as one of the therapy given for their autistic students.